Adjuncting for Life: The Gendered Experience of Adjunct Instructors in Ontario - Nichols, Leslie (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2023)
The market-based imperatives driving economic growth in Western societies have, in ways, both been acknowledged and implicitly used to reorient public institutions - academia dramatically so. This article deals with upending of post-secondary academic hiring priorities, and the impact on the adjunct or sessional lecturers implicated in the change. Over half of the courses offered by academic departments and programs in Ontario, Canada, are now taught by part-time faculty members (Pasma & Shakes, 2018). Their use in post-secondary education is underpinned by a notion of just-in-time course delivery in a free market of untenured PhD holders. This study assessed 26 adjuncts in Ontario, Canada, equally divided between male and female. It found working conditions, development of research dossiers, and health and work-life balance to be characterized by gendered differences and hardships. Although the hardships of post-PhD adjunct work have been abundantly documented, this work brings to light components of the experience that have not been previously studied, most significantly, its health effects and gender nature. It concludes with policy recommendations to support adjuncts in Ontario and beyond, including mentorship, longer term contracts, institutional research funding, extended health benefits, and affordable childcare.